Estresse e síndrome de Burnout em discentes de enfermagem - Goulart, Carolina Tonini (2014)
Understanding the academic training as a pre-professional activity can be considered that college students live with stressors related to the profession and the academic environment. Thus, if students do not opt for effective strategies to cope with the wear, the permanence of stressors can lead to chronicity of stress and in the long term, the Burnout Syndrome. This study aims to determine the association between level of stress and Burnout Syndrome in nursing students from three universities. It is part of a project entitled Stress, Coping, Burnout, and Depressive Symptoms in Hardiness Learners and Teachers of Nursing, registered and approved with the Research Ethics Committee under nº 0380.0.243.000-10. It is an analytical, cross-sectional and quantitative research carried out from a database constructed with data from 571 nursing students from three institutions of higher education in Brazil, two in the Southeast region (one public and one private) and one in the region South (public). Data were collected and partially analyzed in 2011 and 2012, through the form for socio-demographic and academic characteristics of students, the Instrument for Assessing Stress in Nursing Students and the Maslach Burnout Inventory - Student Survey. To test the hypothesis of this study, the chi-square analysis will be performed. P values <0.05 were considered statistically significant, with a confidence interval of 95%. Observed the predominance of female students (84.21%), aged between 20 and 24 years (47.37%), single (74.43%), no children (81.09%) and reside with family (75.61%). Regarding the level of stress there was 55.40% of students in middle stress level and 24.74% indicative for Burnout Syndrome. In the association between level of stress and the occurrence of Burnout Syndrome showed statistically significant difference (p = 0.0380). On the association between stress levels in the areas and Burnout there is a significant statistical difference in the areas Professional Communication (p = 0.0297), and Activity Theory (p = 0.0434). The interaction with the stressors of training can lead to occurrence of burnout. Also we identified students in average level of stress without burnout, which may suggest that these students use strategies to minimize the stressors and thus avoid the syndrome.